PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM STOP STUNTING DI KABUPATEN SIDOARJO - Arif Rahman Nurdianto; Farida Anwari; Acivrida Mega Charisma; Martina Kurnia Rohmah; Khoirun Nisyak (Jurnal SADEWA, 2024)
The problem of stunting is still a health problem that is a major concern for the Sidoarjo Regency government. While the stunting rate at the national level and East Java will decrease in 2022, Sidoarjo Regency shows an increase. In efforts to prevent and overcome stunting, the Sidoarjo Regency government has focused efforts in several villages spread across a number of sub-districts. Furthermore, the aim of this community service activity is to provide education about stunting and its prevention. This community empowerment activity consists of outreach activities to high school students as stunting ambassadors, and training on nutritious food processing attended by PKK cadres in Sidoarjo which is packaged in the Stop Stunting program. The activity method is carried out through coordination with the government, entrepreneurs and educational institutions, counseling of PKK cadres and high school student representatives, as well as training in processing nutritious food ingredients. This activity was attended by 50 students and counseling guidance teachers, as well as 100 PKK cadre mothers in the Sidoarjo area. Overall, the activities in the Stop Stunting program can be implemented well thanks to the cooperation of all related parties. The community service activities that have been carried out are able to increase participants' knowledge about stunting as well as efforts to prevent it, including increasing the ability of PKK cadres to process food ingredients..